The Influence Of Work Style And Generation Z Preferences On Generation Z Performance With Organizational Culture As A Moderating Variable Among Startup Employees In Medan City - Ewy Lady Christin Ritonga; Elisabet Siahaan; Parapat Gultom (Indonesian Journal Publisher, 2025)
The rapid growth of startups in Medan City offers significant opportunities for Generation Z to enter the workforce. However, many startups face challenges in optimizing performance due to limited understanding of Gen Z’s unique work styles and preferences. This study examines the influence of Gen Z’s work style and preferences on performance, with organizational culture as a moderating variable, using a quantitative approach through Partial Least Square Structural Equation Modeling (PLS-SEM). The study surveyed 160 Gen Z employees from various startups in Medan. Results show that work style positively and significantly impacts performance. A flexible, collaborative, and tech-oriented approach enhances task completion. Preferences such as work-life balance, technology use, learning opportunities, and meaningful work also improve performance by increasing engagement and productivity. Moderation analysis reveals that organizational culture negatively moderates the effect of work style on performance—rigid, procedural cultures reduce the benefits of supportive work styles. Conversely, organizational culture positively moderates the influence of preferences on performance. Cultures that value flexibility, collaboration, and innovation strengthen the impact of Gen Z’s preferences. This research supports the Person-Environment Fit and Self-Determination Theory, offering practical insights for startup leaders. Aligning organizational culture and work styles with the values of Generation Z can enhance performance, productivity, and long-term success in the digital era.